Komunikasi Empati Untuk Mengurangi Kasus Bullying Pada Siswa SD Negeri Medokan Semampir - Fatimatus Zahro; Salsabilla Salva Augusta; Insan Romadhan (Institut Nalanda, 2024)
This abstract aims to present an empathetic communication approach as a strategy to reduce bullying cases at Medokan Semampir Elementary School. Bullying among students is a serious issue that requires profound attention from all parties, especially within the school environment. Empathetic communication is key to creating a safe and supportive school environment. This article explains the importance of understanding students' feelings and perspectives to prevent and address bullying cases. The use of empathetic communication techniques, such as active listening, demonstrating understanding, and promoting mutual understanding among students, teachers, and school staff, can help reduce bullying incidents. Through empathetic understanding, it is hoped that a supportive climate can be fostered in the school, where every individual feels valued, heard, and accepted.